Combined influence of fuel injection strategy and nanoparticle additives on the performance and emission characteristics of a biodiesel fueled engine. Issue 1 (1st January 2021) - Kumar, Shiva; Dinesha, Pijakala
Abstract: Waste cooking oil (WCO) biodiesel is becoming promising fuel for compression ignition (CI) engines. Due to the poor thermal efficiency, engine modifications and fuel modifications have been adopted over the years to enhance the performance. In the current study, performance from the biodiesel engine at different injection timing has been studied using waste cooking oil biodiesel mixed with cerium oxide (CeO2 ) nanoparticles as additives. Experiments are conducted at normal injection timing (27 °bTDC), advanced (30 °bTDC) and retarded injection timing (24 °bTDC) using B20 fuel blended with 80 ppm of nanoparticles. Studies indicated that advancing the injection timing, results in higher brake thermal efficiency (BTE) and reduced brake specific fuel consumption (BSFC) for B20 fuel with nanoparticles as compared to fuel without the use of nanoparticles. Smoke, CO and HC emissions reduced on progressing the injection timings, whereas delaying injection timing shows decreased NOx emissions. By advancing the injection timing and adding CeO2 nanoparticles to the blend, BTE is increased by 10.9% and BSFC reduced by 11.1% as compared to the neat B20 biodiesel operation. HC and smoke emissions are 35.4% and 14.2%, respectively, reduced for advancing the injection timing with the adding cerium oxide nano particles to the fuel as compared with clean WCO ester with the absence of nanoparticles. Advancing fuel injection timing has no positive influence on the reduction of NOx.